Work Stress, Teaching Load, and Teaching Satisfaction of Faculty Members in The National University - Joshua C. Ramirez, Mariano; Felicidad R. Dy, Marison (International Journal of Educational Review, 2025)
The importance of managing stress in the work environment has been emphasized as it impacts productivity. This study focused on the relationships among work stress, teaching load, and teaching satisfaction of faculty members at the University of the Philippines Los Baños, Laguna. A total of 147 faculty members from different colleges within the university completed the self-administered questionnaire online. The respondents had an average teaching load of 8.07 for the semester. Generally, they felt slight to moderate pressure and stress (M = 73.55; SD = 25.42). Also, they felt somewhat satisfied with their profession as educators (M = 18.65; SD = 4.76). The relationships among the three variables were determined through Spearman’s rank correlation coefficient. Results showed that work stress has a significant inverse relationship with job satisfaction, r (145) = -.29, p = .000. Also, results showed that teaching load has a significant inverse relationship with job satisfaction, r (145) = -.17, p = .030. Recommendations were made to establish programs to help in managing work stress and ensuring faculty well-being.